Dissecting in Vitro the Activation of Human Immune Response Induced by Shigella sonnei GMMA - Tondi, Serena; Clemente, Bruna; Esposito, Carmen; Sammicheli, Chiara; Tavarini, Simona; Martin, Laura B.; Rossi, Omar; Micoli, Francesca; Bartolini, Erika; Brazzoli, Michela; Ulivieri, Cristina; Blohmke, Christoph J.; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Generalized Modules for Membrane Antigens (GMMA) are outer membrane exosomes purified from Gram-negative bacteria genetically mutated to increase blebbing and reduce risk of reactogenicity. This is commonly achieved through modification of the lipid A portion of lipopolysaccharide. GMMA faithfully resemble the bacterial outer membrane surface, and therefore represent a powerful and flexible platform for vaccine development. Although GMMA-based vaccines have been demonstrated to induce a strong and functional antibody response in animals and humans maintaining an acceptable reactogenicity profile, the overall impact on immune cells and their mode of action are still poorly understood. To characterize the GMMA-induced immune response, we stimulated human peripheral blood mononuclear cells (hPBMCs) with GMMA from Shigella sonnei. We studied GMMA both with wild-type hexa-acylated lipid A and with the corresponding less reactogenic penta-acylated form. Using multicolor flow cytometry, we assessed the activation of immune cell subsets and we profiled intracellular cytokine production after GMMA stimulation. Moreover, we measured the secretion of thirty cytokines/chemokines in the cell culture supernatants. Our data indicated activation of monocytes, dendritic, NK, B, and γδ T cells. Comparison of the cytokine responses showed that, although the two GMMA have qualitatively similar profiles, GMMA with modified penta-acylated lipid A induced a lower production of pro-inflammatory cytokines/chemokines compared to GMMA with wild-type lipid A. Intracellular cytokine staining indicated monocytes and dendritic cells as the main source of the cytokines produced. Overall, these data provide new insights into the activation of key immune cells potentially targeted by GMMA-based vaccines.